Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Fu, Hongli; Dan, Bo; Gao, Zhigang; Wu, Xinrong; Chao, Guofang; Zhang, Lianxin; Zhang, Yinquan; Liu, Kexiu; Zhang, Xiaoshuang; Li, Wei (Frontiers in Marine Science, 2023)
We present version 2 of the China Ocean ReAnalysis (CORA2) in this paper. We compare CORA2 with its predecessor CORA1, and with other ocean reanalysis products (GLORYS12v1, HYCOM, GREP, SODA3, and ECCO4) during 2004-2019, to show its improvement and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved due to enhanced resolution to 9 km and updated data assimilation scheme, when compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products. The subsurface temperature (salinity) RMSE of CORA2 at 0.87°C (0.15 psu) is comparable to that of SODA3, smaller than that of ECCO4 and larger than those of GLORYS12, HYCOM and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variabilities of subsurface temperature and salinity compared with the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region as GREP and GLORYS12v1 do, it is better than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations of steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of steric sea level of CORA2 is closer to that of GREP compared with the other products; and the long-time warming trends of global OHC in the high-resolution CORA2 and GLORYS12 are larger than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it becomes good from 2009 onward. We plan to further improve CORA2 by assimilating available best observation data, using the incremental analysis update (IAU) procedure and improving SLA assimilation method.